#TITLE_ALTERNATIVE# - GUMILAR (NIM: 20715018), ANGGI
Olive oil is an oil that was widely used in various fields of good health, food, and cosmetics. Extra virgin olive oil has an expensive price that becomes a target of adulteration of oil at a cheaper price. Adulteration of olive oil was widespread, very organized. Based on Pharmacopoeia Indonesia edition V the detection of other oils in olive oil were done by chemical method which requires a lot of organic solvent, a long time, and difficult to do. In this research, the analysis of adulteration extra virgin olive oil by using infrared spectrofotometry and spectrofluorometry with chemometric aid such as Principal Component Analysis (PCA) and cluster analysis, furthermore the quantitative analysis also performed using Partial Least Square (PLS) method. The results of this study indicate that infrared spectrofotometry and spectrofluorometry methods can be used in detecting olive oil adulteration. Infrared spectrophotometry method gave the good result in quantitative analysis due to the value of R2, RMSEC, and RMSEV compared to spectrofluorometry method. Samples obtained from supermarkets in Bandung probably there were not adulteration because based on the results of the principal component analysis has a close distance. Moreover the cluster analysis using infrared spectrophotometry method also showed similarity levels above 90% .